2015
DOI: 10.1038/srep14442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of conventional laparoscopic radical prostatectomy by the transperitoneal versus extraperitoneal procedure

Abstract: Worldwide, prostate cancer (PCa) is the second most common malignancy in males. We undertook a meta-analysis to compare the efficacy and safety of conventional laparoscopic radical prostatectomy with a transperitoneal (TLRP) approach, versus that of an extraperitoneal (ELRP) approach, for treatment of localized PCa. A comprehensive literature search retrieved 14 publications, with a total of 1715 patients. Meta-analysis of these studies showed that an ELRP approach was associated with a significantly shorter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, this systematic review and meta-analysis is the first study to comprehensively evaluate this topic. The previous reviews or systematic reviews or meta-analysis evaluated the techniques of RP 5 , 18 20 (such as RARP, laparoscopic, and retropubic open), the PSM and perioperative complication rates of primary surgical treatments 21 , the primary surgical treatments for prostate cancer 22 26 , transperitoneal and extraperitoneal robot-assisted RP 27 , and the efficacy and safety of conventional laparoscopic RP with a transperitoneal approach versus that of an extraperitoneal approach 28 . Therefore, none of these studies focused on the surgical technique of RP.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this systematic review and meta-analysis is the first study to comprehensively evaluate this topic. The previous reviews or systematic reviews or meta-analysis evaluated the techniques of RP 5 , 18 20 (such as RARP, laparoscopic, and retropubic open), the PSM and perioperative complication rates of primary surgical treatments 21 , the primary surgical treatments for prostate cancer 22 26 , transperitoneal and extraperitoneal robot-assisted RP 27 , and the efficacy and safety of conventional laparoscopic RP with a transperitoneal approach versus that of an extraperitoneal approach 28 . Therefore, none of these studies focused on the surgical technique of RP.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of EBL, the transperitoneal patients had less blood loss than the extraperitoneal patients (800 mL vs. 400 mL, respectively, p < 0.001). Some other studies comparing EBL between E-LRP and T-LRP reported discrepancies; however, they found less blood loss, for which a possible explanation is the ergonomic space [19][20][21]. One possibility is an ergonomic space of the intraperitoneal cavity can exert enough pressure on the surrounding tissue to suppress bleeding, and one possible explanation for the signifcant diference in blood loss is that in the transperitoneal group, a considerable amount of blood was retained among the bowel loops.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a preliminary conclusion can be drawn that more EBL is tightly associated with the transperitoneal route, similar results can be found in some previous studies which compare EBL between Ep-LRP and Tp-LRP (25-27). One possibility is that a self-made gas bag can make enough pressure on the surrounding tissue to lower the bleeding in extraperitoneal route (28).…”
Section: Discussionmentioning
confidence: 99%